Peningkatan Kemampuan Anak Mengenal Bentuk Geometri Melalui Tari Kreasi di Taman Kanak -Kanak Islam Yannira Padang - Nuzra, Prima; Wirman, Asdi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
The problem of reserch was “ the low of chlidren ability to recognize the geometric shapes. The research aims to see how the creative dance can improve the geometric in the children abilities in the Yannira Islamic Kindergarten. The research took a sample of 15 children. All the data is collected and the analized. The research method was Classroom Action Research (CAR).From the research it can be concluded that The Creative Dance can improve the children ability to recognize geometricshapes